Community Participation In Building An Effective Ethics And Public Accountability System In Indonesia - Salamatul Afiyah; Cici Nasirotul Maspufah; Dini Nun Anggraeni (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2023)
Abstract The high level of problems in building an effective system of ethics and public accountability, such as corruption, nepotism, and limited access to public information, are obstacles to the growth and progress of the country. The purpose of writing this article is to discuss the development of an effective ethical and public accountability system in Indonesia. The method in this study uses a qualitative approach that is descriptive using the library study method taken from various sources of articles, journals and books as well as news related to related issues. The results of this study indicate that lack of transparency, oversight, disregard for law, and problems of corruption have slowed the development of an effective system of ethics and public accountability in Indonesia. Solutions that can be implemented include strengthening laws and regulations, strengthening public institutions, increasing transparency and access to public information, increasing community participation, and increasing public awareness. It is hoped that the development of an effective system of ethics and public accountability can help create a conducive environment for economic growth and people's welfare in Indonesia. Keywords : Community Participation, Ethical System Building, Public Accountability.